Positive, Open, Proud: an adapted disclosure-based intervention to reduce HIV stigma - Chenneville, Tiffany; Kosyluk, Kristin; Gabbidon, Kemesha; Franke, Molly; Serpas, Dylan; Galea, Jerome T. (Frontiers in Global Women's Health, 2024)
HIV stigma among people living with HIV (PLWH) is well documented and linked to adverse physical and mental health outcomes among this population. Further, stigma may affect HIV disclosure decisions, which has important individual and public health implications. For women, HIV stigma and disclosure may be compounded by gender-based discrimination and violence. Despite the ill effects of HIV stigma, particularly for women, few evidence-based disclosure interventions to reduce stigma among PLWH exist. However, there is strong evidence for the efficacy of Honest, Open, Proud (HOP), a disclosure-based stigma-reduction intervention for people with mental illness. Given that mental illness and HIV are similar in that they are both stigmatized yet concealable conditions, we propose using the ADAPT-ITT model to adapt HOP into Positive, Open, Proud, a disclosure-based stigma-reduction intervention for PLWH, describing its unique potential for women living with HIV.